Towards a Blue Revolution: water harvesting in Nicaragua - International Center for Tropical Agriculture (2011)
How do you transform landscapes and livelihoods in just one year? Water harvesting pilot projects in drought-prone Nicaragua are proving that crop yields and farm incomes can be boosted significantly and very quickly, with relatively simple technology. These FLAR-coordinated projects, funded by the Common fund for Commodities (CFC), are also underway in Mexico and Costa Rica, with great potential for expansion in Central America. For more info contact www.flar.org